Genetic identification of effectors downstream of Neu (ErbB-2) autophosphorylation sites in a Drosophila model. - Settle, M.; Gordon, M.D.; Nadella, M.; Dankort, D.; Muller, W.; Jacobs, J.R. (Oncogene, 2003)
The ErbB-2/Neu receptor tyrosine kinase plays a causal role in tumorigenesis in mammals. Neu's carboxyl terminus contains five phosphorylated tyrosines that mediate transformation through interaction with cytoplasmic SH2 or PTB containing adaptor proteins. We show that Drosophila adaptors signal from individual phosphotyrosine sites of rat Neu. Activated Neu expression in the midline glia suppressed apoptosis, similar to that seen with activated Drosophila EGF-R expression. Expression in eye and wing tissues generated graded phenotypes suitable for dosage-sensitive modifier genetics. Suppression of ErbB-2/Neu-induced phenotypes in tissues haplosufficient for genes encoding adaptor protein or second messengers suggests that pTyr 1227(YD) signals require Shc, and that pTyr 1253 (YE) signalling does not employ Ras, but does require Raf function. Signalling from pTyr (YB) was affected by a haplosufficiency in drk (Grb-2), and in genes thought to function downstream of Grb-2: dab, sos, csw (Shp-2), and dos (Gab-1). These data demonstrate the power of Drosophila genetics to unmask the molecules that signal from oncogenic ErbB-2/Neu.